2017
DOI: 10.1016/j.fct.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of tea, red wine and cocoa in diabetes. Evidences from human studies

Abstract: Prevention of diabetes through the diet has recently received an increasing interest, and polyphenolic compounds, such as flavanols, have become important potential chemopreventive natural agents due to their proved benefits on health, with low toxicity and cost. Tea, red wine and cocoa are good sources of flavanols and these highly consumed foods might contribute to prevent diabetes. In this regard, there is increasing evidence for a protective effect of tea, red wine and cocoa consumption against this disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 125 publications
0
32
0
Order By: Relevance
“…In humans and animal models, flavanols or flavanols-rich foods (mainly, cocoa or tea derivates) have demonstrated the ability to reduce body weight, decrease waist circumference and fat percentages, improve glucose metabolism in individuals with type 2 diabetes, obesity or MetS and increase energy expenditure [ 75 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. One of the most described molecular mechanism underlying theses effects are the activation of the AMPK enzyme [ 140 ].…”
Section: Flavanolsmentioning
confidence: 99%
“…In humans and animal models, flavanols or flavanols-rich foods (mainly, cocoa or tea derivates) have demonstrated the ability to reduce body weight, decrease waist circumference and fat percentages, improve glucose metabolism in individuals with type 2 diabetes, obesity or MetS and increase energy expenditure [ 75 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. One of the most described molecular mechanism underlying theses effects are the activation of the AMPK enzyme [ 140 ].…”
Section: Flavanolsmentioning
confidence: 99%
“…In this regard, growing evidence suggests the anti-diabetic activity of cocoa by contributing to control glucose levels (Cordero-Herrera, I. et al, 2015, Costa, C. et al, 2017, Grassi, D. et al, 2008, Jalil, A.-M.-M. et al, 2008, Martín, M.A. et al, 2016, Martín, M.A. et al, 2017, Ruzaidi, A. et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2006), and have shown beneficial effects against diabetes in humans (Costa, C. et al, 2017, Grassi, D. et al, 2008, Kim, Y. et al, 2016, Martín, M.A. et al, 2016, Martín, M.A. et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of flavanol-rich dark chocolate (102) and supplementation with epicatechin (103) improve insulin sensitivity in healthy subjects. Importantly, numerous epidemiological studies and RCT have demonstrated that consumption of green tea, red wine and cocoa lowers the risk of type 2 diabetes (108) . In addition, higher consumption of anthocyanins and anthocyanin-rich fruit has also been associated with lower risk of type 2 diabetes (104) .…”
Section: Human Intervention Studiesmentioning
confidence: 99%